Human relations in organizations : - Lussier, Robert N. (McGraw-Hill Irwin, 2010)
Offers a three-pronged approach: an understanding of human relations/ organizational behavior concepts; the application of HR/OB concepts for critical thinking in the business world; and, the development of HR/OB skills. This book is suitable for professors who want to incorporate activities and exercises into the classroom.